The Ideas and Concepts of Overture Music Composition: One of the Opera Music Compositions of Kehidupan Dua Zaman Hikayat Siboru Deakparujar on the Creation of New Mode and Rhythm of Ogung Instrument - Junita Batubara (SCAD Independent, 2017)
The main problem in the composition idea of Overture is the studying of Opera itself but very few works of opera compositions that combine Western music with the traditional music of the Batak Toba Indonesia. Second, in the traditional opera of Batak Toba, it is often performed musical themes taken from the social life story of Batak Toba society and it is extremely rare, especially among the people of Batak Toba. Third, in the Batak opera, the music is used only as an entertainment and separated from the content of the story and often does not have the music score. The Overture created uses Atonality scale inspired by the pentatonic music of Batak Toba by using music score. Fourth, collecting information related to the influence of Western music, in this case, Atonality and pentatonic music of Batak Toba. Fifth, The use of the musical elements such as melody, rhythm pattern, tone color, harmony, form, texture and orchestra. With the above description, the writer created an opera based on the employment elements of Western music and Batak Toba music. The author made the employment of methods with the use of a rhythmic pattern on traditional musical instruments ogung and sulim combined with Western musical instrument without changing each ton of each musical instrument of the traditional Batak Toba. Sixth, the mode of pentatonic (five pitch) in which five pitch is the texture of taganing mode in the ensemble of gondang hasapi (an ensemble of the traditional music of the Batak Toba, North Sumatra in Indonesia) that are customized according to the tuning system of twelve of Western music pitch in order to generate new modes used in the above employment of opera.